2022
DOI: 10.1021/acscatal.2c03200
|View full text |Cite
|
Sign up to set email alerts
|

Environment Molecules Boost the Chemoselective Hydrogenation of Nitroarenes on Cobalt Single-Atom Catalysts

Abstract: Single-atom catalysts (SACs) have received intensive interest due to the utmost atom utilization and unique catalytic behaviors. However, the catalytic mechanism of SACs is still unclear, especially in the reactions involving multiple substrates. Here, we report that the environment moieties, protic solvents, and external bases can boost the cobalt SAC-catalyzed chemoselective hydrogenation of nitroarenes. Systematical studies clearly reveal that the heterolysis of H2 between the metal center and the neighbori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 93 publications
0
13
0
Order By: Relevance
“…A similar trend was also observed in the activation of the second H 2 molecule and subsequent hydrogenation process during the VII to IX steps. In addition, H 2 /D 2 kinetic isotope effect (KIE) experimental results (Figure b and Figure S32) show large values of k H / k D exceeding 4.5 for all catalysts, confirming that the RDS involves H 2 heterolytic dissociation or H* atom transfer, which is consistent very well with DFT calculation results and the reported H 2 dissociation manner on other SACs in the literature. ,, …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar trend was also observed in the activation of the second H 2 molecule and subsequent hydrogenation process during the VII to IX steps. In addition, H 2 /D 2 kinetic isotope effect (KIE) experimental results (Figure b and Figure S32) show large values of k H / k D exceeding 4.5 for all catalysts, confirming that the RDS involves H 2 heterolytic dissociation or H* atom transfer, which is consistent very well with DFT calculation results and the reported H 2 dissociation manner on other SACs in the literature. ,, …”
Section: Resultsmentioning
confidence: 99%
“…Experimental and DFT calculation results disclosed that the adsorption and desorption strength of the activated H* atoms on Ir single atoms was a key factor for the Sabatier phenomenon. Different from a great number of studies focusing on the regulation coordination environments of SACs, ,, this work emphasizes how the single-atom density affects the electronic structures of central metal atoms and their catalytic performances in hydrogenation reactions. We notice that the neighboring single sites could indeed work in synergy to further enhance the reactivity of SACs in various reactions in recent publications. ,, However, the mechanism behind such effects was different in various reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a similar templateassisted pyrolysis strategy was applied to synthesize SACs as well. [86][87][88][89][90][91][92] A summary of the discussed preparation strategies is displayed in Table 1 detailing principles, uniqueness, and respective advantages and disadvantages.…”
Section: Other Strategiesmentioning
confidence: 99%
“…Meanwhile, the kinetic isotope experiments showed a lower times (1.22−1.45) of C�O hydrogenation rate under the D 2 atmosphere than that under the H 2 atmosphere (Figure S8E,F), which further indicates that the H 2 activation step is rapid and not significantly included in the rate-determining step. 44,45 Previous studies have reported that intermetallic catalysts promote selective hydrogenation, such as the C�C semihydrogenation of alkynols or acetylene to form enols or olefins, 28,46 C�C hydrogenation of 1,3-butadiene to 1-butene, 47 hydrogenation of CO 2 to methanol, 29 NO 2 hydrogenation of nitrophenols to aminophenols, 48 and Nmethylation of N-methylaniline to N,N-dimethylaniline 49 in organic solvents or solvent-free conditions via surface geometric and electronic effects. Furthermore, reactions conducted in isopropanol and cyclohexane only generated C�O hydrogenated MFA with a selectivity of 99.9%; however, the MF conversion rates were <20% (Figure S8I).…”
Section: Identification Of Hydrogenation Sitesmentioning
confidence: 99%